(untitled) (Economics and region, 2018)
The purpose of the article is to make proposals on the improvement of international norms of the delivery of information about the land (land parcels) in financial statements. In order to improve the quality of relevant information on land parcels for users (investors and creditors), it is proposed to improve the international standards of financial reporting as follows: based on the unique nature of the land (property) as a type of assets of economic entities, to introduce the «Land» (or «Land and buildings») article into the minimum list of articles of the Statement of Financial Position, that should includes all the land (or land and buildings) held by the owner and leased, with the exception of land (or land and buildings) held for sale, with the relevant general evaluation models. Considering that the cost of land is not depreciated to propose, for the book valuation of land parcels held for the purpose of long-term use, to apply a fair value model, which is currently allowed by international standards to choose accounting policy only for investment property. It is given the fundamental importance for investors and creditors of the classification of assets in the Statement of Financial Situation for current and non-current, in particular for the indicator of «Working capital», to display the land for sale in the current assets segment, but at the net realizable value.